Acute Respiratory Infection Hubs: A Service Model with Potential to Optimise Infection Management - Sarah Jawad; Anna Buckingham; Charlotte Richardson; Aoife Molloy; Bola Owolabi; Matt Inada-Kim (MDPI AG, 2023)
Patients with acute respiratory infections (ARI)-including those with upper and lower respiratory infections from both bacterial and viral pathogens-are one of the most common reasons for acute deterioration, with large numbers of potentially avoidable hospital admissions. The acute respiratory infection hubs model was developed to improve healthcare access and quality of care for these patients. This article outlines the implementation of this model and its potential impacts in a number of areas. Firstly, by improving healthcare access for patients with respiratory infections by increasing the capacity for assessment in community and non-emergency department settings and also by providing flexible response to surges in demand and reducing primary and secondary care demand. Secondly, by optimising infection management (including the use of point-of-care diagnostics and standardised best practise guidance to improve appropriate antimicrobial usage) and reducing nosocomial transmission by cohorting those with suspected ARI away from those with non-infective presentations. Thirdly, by addressing healthcare inequalities; in areas of greatest deprivation, acute respiratory infection is strongly linked with increased emergency department attendance. Fourthly, by reducing the National Health Service's (NHS) carbon footprint. Finally, by providing a wonderful opportunity to gather community infection management data to enable large-scale evaluation and research.